Evaluation of Varicocelectomy Operative Therapy for Infertile Couples at the UGM Academic Hospital - Sp.U, WIKAN KURNIAWAN (Rumah Sakit Akademik Universitas Gadjah Mada, 2023)
Background: Infertility is a condition of the male or female reproductive system characterized by failure to achieve pregnancy after 12 months or more of having regular sexual intercourse without contraception. Since 2013, Rumah Sakit Akademik UGM (RSA UGM) has providing varicocele therapy to infertile individuals. The Ivanissevich varicocelectomy procedure is used for varicocele therapy.Objective: This study intends to examine the management of varicocele patients at RSA UGM.Methods: This research is a retrospective study by opening medical records and interviews. The study population was all patients who underwent varicocelectomy surgery between 2013 and 2021. Data is presented in the form of graphs.Results: The distribution of varicocele lateralization showed that out of 35 respondents, 23 respondents (66%) had one side varicoceles and 12 respondents (34%) both sides varicoceles. The distribution based on successful pregnancy shows that out of 35 respondents, 10 respondent couples (29%) have already gotten pregnant, 25 respondents (71%) haven't gotten pregnant. The distribution of varicocele lateralization in respondents who have children shows that 70% of respondents are one side and 30% of respondents are both sides. Complications of discomfort revealed that 88% of research participants had no complaints of postoperative pain, whereas 11% occasionally suffered pain following varicocele surgery.Conclusion: Varicocele that is one side is more common. Patients with one side varicocele who have surgery are more likely to become parents than those with both sides varicocele. At RSA UGM, the varicocelectomy success rate is comparable to the worldwide success rate.Keywords: Varicocele, success rate, one side, both sides.